ONLINE CONSUMER BEHAVIOR AND SOCIAL MEDIA MARKETING IMPACT - Kaurabhatti, Chan Preet; Shrivastava, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction:People now spend their whole lives online. Internet access used to be a novelty, but now days it's a need that can't be avoided. Whether it is business, social connection or commerce, the Internet is a part of every aspect of our lives. In addition, people's lifestyles have altered, resulting in a movement from conventional to digital ways of doing things, such as online shopping. Aim of the study: The Main Aim of The Study Is to Online Consumer Behavior and Social Media Marketing Impact Material and method: Starting with the issue description, the current study aims to get an in-depth knowledge of how students at "Deemed university" University in India interact with social media, namely on Facebook and Twitter. Conclusion: There are certain limitations to this study that might lead to new paths of inquiry. Firstly, the selection of the sample and the measurement of the variables utilised have certain constraints. Students from India were used as a sample for this study's research.